Analisis Minat Penggunaan Dompet Digital LinkAja Menggunakan Theory of Reasoned Action - Utami, Mutiara Gunawan; Dermawan, Moulvi; Yusuf, Abdul (Universitas Proklamasi 45, 2023)
The use of digital payment systems is increasing in recent times. Digital payment systems allow users to make payments more easily and practically through their smartphones. LinkAja is a digital wallet application that allows us to make various transactions online. This study was conducted to examine what influences interest in using the LinkAja application and the influence of subjective intentions, attitudes, and norms on interest in using it. The theory that underlies this research is the Theory of Reasoned Action (TRA). The method used is a quantitative research method, the research data come from the results of a questionnaire filled out by 40 LinkAja users from several cities in the provinces of Jakarta and West Java. The sampling technique is probability sampling and simple random sampling. Testing and data processing is done using SPSS. The results obtained in this study state that the Intentions, Attitudes, and Subjective Norms together (simultaneously) have a significant influence on the Interest in Using the LinkAja Digital Wallet application.